Factors Affecting the Sustainability of Telecentres in the Developing Country - Do Manh Thai; Dang Duong; Morten Falch; Chung Bui Xuan; Tran Thi Anh Thu (International Telecommunications Society (ITS), 2021)
Due to rapid technological changes, governments in developing countries have paid special attention to sustainability. However, understanding insights into the sustainability of telecentres remains an open question. This paper aims to fill this gap. We conducted a case study in Vietnam by using both qualitative and quantitative data. We used the Kumar and Best's (2006) model as our theoretical lens to analyse the sustainability of telecentres in Vietnam. The paper finds that telecentres have shifted their concept to provide a wide range of services, both online and offline. The paper indicates that technological, political, and social sustainability are important for the sustainability of telecentres. The paper recommends that we should take the role of state-owned enterprises and the digital transformation at telecentres into consideration to sustain telecentres. Furthermore, the paper indicates the mutual relation between political and technical sustainability with social sustainability that has not been yet unveiled in the prior literature.
Keywords: 330; telecentres; cultural-post offices (CPOs); sustainability; digital transformation; Vietnam